2022
DOI: 10.3389/fmars.2022.880337
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Melanin in the Mantle of the Pacific Oyster Crassostrea gigas

Abstract: The Pacific oyster, Crassostrea gigas, is widely distributed and is substantially important to shellfish cultivation. Oysters with melanin-colored shells and soft parts are increasingly popular and are of high economic value. However, the distribution and synthesis of melanin in C. gigas remains unclear and there have been only few relevant studies on it. In this study, transmission electron microscopy (TEM) was used to observe melanin in the epidermis of dark mantle tissue. Melanocytes containing melanosomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…A significant La–Ca interaction and La–Ca–Cd interplay on the accumulation of Cd were found in wheat (Table ). La shares physical similarity with Ca and Cd. , A previous study indicated that La can bind with CaM . CaM alters its conformation and dynamics upon binding with La 3+ .…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…A significant La–Ca interaction and La–Ca–Cd interplay on the accumulation of Cd were found in wheat (Table ). La shares physical similarity with Ca and Cd. , A previous study indicated that La can bind with CaM . CaM alters its conformation and dynamics upon binding with La 3+ .…”
Section: Discussionmentioning
confidence: 97%
“…Likewise, similar results were observed in the present work (Figure ), and there was a significant La–Cd interaction on Cd accumulation in wheat (Table ). For the phenomenon, a possible reason is the competition between La and Cd for adsorption and absorption sites because of their similar ionic radius. , Likely, another reason underlying a significant La–Cd interaction on Cd accumulation in wheat could be related to La decreasing Cd uptake and upward translocation through the downregulation of TaNramp5 and TaHMA2 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations